Studies of the Bradyrhizobium japonicum nodD1 promoter: a repeated structure for the nod box. - Wang, S P (1991)
Induction of nod genes in Rhizobium and Bradyrhizobium species is dependent on the presence of plant-produced flavonoids, the NodD protein, and the cis-acting nod box promoter sequence. Although the nodD (nodD1) gene in Rhizobium species is constitutively expressed, nodD1 expression in Bradyrhizobium japonicum is inducible by isoflavones in a manner similar to that of the nodYABC operon. A consensus nod box sequence is found 5' of the nodYABC operon, whereas a presumptive, nod box-like sequence is found 5' of the nodD1 gene. As an initial step toward examining the nodD1 promoter, the transcriptional start sites of the nodD1 and nodYABC operons were determined and found to be 44 and 28 bp, respectively, downstream of their respective nod box sequences. A series of deletions of the nodD1 promoter were constructed and fused to the lacZ gene. Analysis of the activity of these deletions clearly showed that the divergent nod box sequence was essential for nodD1 induction by isoflavones or soybean seed extract. The induction of nodD1 expression requires NodD1, as tested in B. japonicum and in a heterologous system, Agrobacterium tumefaciens. On the basis of these data, we analyzed the published nod box sequences and propose a new consensus sequence composed of paired 9-bp repeats. Analysis of the nodD1 nod box and synthetic constructs of the nocYABC nod box indicate that at least two 9-bp repeats are required for NodD1-mediated induction. Furthermore, insertions between the paired repeats of the nodYABC nod box suggest that orientation of the repeats on opposite faces of the DNA helix is essential for maximum nod gene expression.